Dynamic anterior shoulder stabilization using the long head of the biceps tendon: a biomechanical study: DAS: a biomechanical study. Issue 5 (31st May 2019) - Mehl, J.; Imhoff, F.; Obopilwe, E.; Dyrna, F.; Lädermann, A.; Collin, P.; Arciero, R.A.; Beitzel, K.; Mazzocca, A.
Objectives: A new concept of dynamic anterior shoulder stabilization (DAS) combining Bankart repair with the additional sling effect of the long head of the biceps (LHB) tendon to treat anterior glenohumeral instability has recently been introduced. The purpose of this study was to biomechanically investigate the stabilizing effect of the DAS technique in comparison to standard Bankart repair in different defect models. Methods: Twenty-four fresh frozen cadaver shoulders (average ± SD: age 60.1 ± 8.6 years) were mounted in a shoulder-testing system allowing 6 degrees of freedom. According to cross sectional area ratios the rotator cuff muscles and the LHB tendon were loaded with 40 N and 10 N, respectively. Glenohumeral translation was tested in 60° abduction and 60° external rotation (ABER position) while forces of 20 N, 30 N and 40 N were applied. The translation was measured using a 3D-digitizer and the total translation and the relative translation in relation to the native starting position were determined. Maximal external and internal rotation after application of 1.5 Nm torque to the humerus were measured. All specimens went through for 4 different conditions (Intact, defect, isolated Bankart repair, DAS) and were randomized to 3 different defect groups (Isolated Bankart lesion; 10% anterior glenoid defect; 20% anterior glenoid defect). Results: Both surgical techniques resulted in decreased anterior glenohumeral translation in comparison to the defect conditions in all defect groups. In comparison with isolated Bankart repair DAS showed significant less relative anterior translation in 10% glenoid defects (30 N: 2.6 ± 3.4 mm vs. 5.3 ± 4.2 mm; p=0.044) and in 20% glenoid defects (40 N: 2.1 ± 6.6 mm vs. 6.0 ± 5.7 mm; p=0.035). However, in 20% defects DAS led to a relevant posterior and inferior shift of the humeral head in ABER position and to a relevant increase of inferior glenohumeral translation. Both surgical techniques did not limit the rotational range of motion. Conclusion: In the context of minor glenoid bone defects the DAS technique demonstrates superior results in comparison to isolated Bankart repair.